Multilingual Communication and Intercultural Adaptation Among Indonesian Diaspora Students in Davao - Lumban Arofah; Rochgiyanti; Syahlan Mattiro; Laila Azkia; Nasrullah; Alfisyah; Yuli Apriati; Muhammad Barto Maulana Irsyad Baso (FAKULTAS DAKWAH UIN SALATIGA, 2026)
This study examines multilingual communication practices and intercultural adaptation among Indonesian diaspora students at Sekolah Indonesia Davao (SID), a government-sponsored Indonesian school in Davao City, Mindanao, Philippines. Grounded in intercultural communication theory, specifically Gudykunst and Kim’s (2003) cross-cultural adaptation model, Ting-Toomey’s (1999) face-negotiation theory, and Deardorff’s (2006) intercultural competence framework, the study investigates how SID students deploy multilingual communication repertoires as strategies for intercultural adaptation and identity negotiation in a complex four-language ecology (Indonesian, English, Filipino, and Bisaya). Using a descriptive quantitative design with supplementary qualitative analysis, data were collected from ten purposively selected students (grades 9–12) through a validated 27-item bilingual questionnaire. Results reveal that (1) 90% of respondents engage in multilingual communication switching, with a trilingual Indonesian–English–Filipino/Bisaya pattern dominating (60%), reflecting achieved intercultural communicative competence rather than linguistic deficiency; (2) habit is the primary communication motivation (70%), indicating that multilingual switching has been internalized as an unmarked communicative norm; (3) a polyglossic communication structure pertains, with Indonesian dominating formal institutional contexts and mixed codes functioning as the face-affirming, solidarity-building register of informal interaction; (4) 60% of respondents demonstrate high metalinguistic awareness of their communication practices; and (5) all respondents affirm that multilingual communication competence contributes positively to intercultural adaptation in Davao. Beyond individual switching, the study identifies an emergent community-level communication code, a shared trilingual variety functioning simultaneously as a diasporic identity marker. These findings contribute to interdisciplinary communication science by demonstrating that multilingual communication practices in diaspora school communities constitute sophisticated intercultural competence strategies, and carry direct implications for intercultural communication-informed language education policy in overseas Indonesian schools (SILN).